Review of studies on cross-country skiing footwear - Hladnik, J.; Jerman, B. (7th International Students Symposium on Logistics and International Business, Plzen, Czech Republic, November 6-10, 2017, 2017)
Scientific approach conducted with computer technology and measurements is necessary in development of cutting edge competitive cross-country skiing footwear. The paper provides a brief review on FE studies made on such footwear. In those studies recommendations on boot construction changes were given in order to increase the boots stiffness-mass ratio and consequently their energetic efficiency. In continuation of the present paper advice for further studies on cross-country skiing footwear is given.